Efficiency of gluing products made from thermal modified wood - TSAPKO, Yuriy; TSAPKO, Alexey; BONDARENKO, Olga; ANOPKO, Dmitry; KAVERIN, Kostyantin (Ways to Improve Construction Efficiency, 2025)
was found that the manufacture of glued products causes certain difficulties in ensuring adhesion. One of the promising areas of use of thermally modified wood is the manufacture of glued products. Therefore, knowledge of the physical and mechanical properties of thermally modified wood, its quality indicators, adhesion with organic adhesives allows you to make a choice taking into account economic indicators, duration and safety of use. In addition, during the modification of wood, the process of polymerization and redistribution occurs in the cell volume and gives the cell walls greater density, hardness, increases hydrophobicity (water repellency), thereby reducing their ability to absorb moisture and swell. As a result of experimental studies, it was found that the nature of the destruction for the entire group of samples based on glue is the same. The additional effect of temperature or humidity did not show a significant difference compared to the control samples. It was established that in samples of untreated ash wood and modified at temperatures of 160, 220°C, the destruction occurs along the glued layer. The results of the research will allow us to solve further problems regarding the creation of new composites from thermally modified wood and the conditions of their operation at different facilities. It was established that the nature of the destruction for the entire group of samples based on glue is the same. The additional effect of temperature or humidity did not show any significant difference, compared to the control samples. It was established that in samples of untreated ash wood and modified at temperatures of 160, 220°C, the destruction occurs along the glued layer. The results of the research will allow us to solve further problems regarding the creation of new composites from thermally modified wood and the conditions of their operation at different facilities.